1996
DOI: 10.1080/10473289.1996.10467512
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Investigation of Heavy Metal Removal by Soil Washing

Abstract: The purpose of this study was to explore the influence of organic matter in soils while removing heavy metals by sodium metabisulfite and EDTA solutions. The results obtained show that both sodium metabisulfite and sodium EDTA solutions have good removal efficiencies of zinc and lead. However, sodium metabisulfite was effective in extracting lead from a low organic content silty clay soil, and 0.05 M EDTA solution was a better extraction agent for soils with high organic matter content. These preliminary exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 0 publications
0
44
0
Order By: Relevance
“…High organic-matter content in the soil affects the washing processes because the high molecular weight humus organic substances have a high affinity for metals and form water-insoluble metal complexes (Peters, 1999). Influence of organic matter on the removal of heavy metals by soil washing techniques employing sodium metabisulfite and EDTA solutions is reported (Abumaizar and Khan, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…High organic-matter content in the soil affects the washing processes because the high molecular weight humus organic substances have a high affinity for metals and form water-insoluble metal complexes (Peters, 1999). Influence of organic matter on the removal of heavy metals by soil washing techniques employing sodium metabisulfite and EDTA solutions is reported (Abumaizar and Khan, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…High organic-matter content in the soil affects the washing processes because the high molecular weight humus organic substances have a high affinity for metals and form water-insoluble metal complexes (Peters, 1999). Influence of organic matter on the removal of heavy metals by soil washing techniques employing sodium metabisulfite and EDTA solutions is reported (Abumaizar and Khan, 1996).The present study evaluates and compares the effectiveness of different biodegradable APCs for 4 the washing treatment of organic-rich soil with that of EDTA. The biodegradable APCs are: EDDS, imminodisuccinic acid (IDSA), methylglycinediacetic acid (MGDA), DL-2-(2-carboxymethyl) nitrilotriacetic acid (GLDA) and 3-hydroxy-2,2'-iminodisuccinic acid (HIDS).…”
mentioning
confidence: 99%
“…Extensive evaluations of numerous chelating agents have shown that EDTA is one of the most effective solubilizing agents for many metals, including Pb, Cd, Zn, and Mn. [3][4][5][6] Kent et al 7 and Davis et al 8 have conducted tracer tests with several metal-EDTA species. Jardine et al 9 studied the reactions of metal-EDTA species in column systems packed with natural aquifer materials.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 They are also encountered in wash solutions from the remediation of metal-contaminated soils. 3,4 It has been recognized that the presence of strong complexing agents such as EDTA (ethylenediaminetetraacetic acid), NTA (nitrilotriacetic acid), citrate, and oxalate cannot be handled satisfactorily using conventional chemical precipitation or coagulation processes such as hydroxides and sul®des. 5 In addition, the high buffer capacity provided by the complexing agents requires excessive amounts of chemicals to neutralize the alkalinity.…”
Section: Introductionmentioning
confidence: 99%